The role of genital tract infection inpreterm delivery: aretrospective study - Susilawati, Tri Nugraha; Satria, Yohanes Aditya Adhi; Budihastuti, Uki Retno (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2019)
Preterm delivery is associated with higher mortality and morbidity of neonates, also increasestheir risk of having growth and development impairment.This study aimed toidentify the role ofgenital tract infection in preterm delivery. A retrospective study was conducted on medical records of mothers who had preterm delivery in a tertiary hospital in Surakarta, Indonesia during 2017. The data collected were mothers’ age and their gestational age, the history of current pregnancy, the number of previous abortion(s), mothers’ body temperature, the extent of abnormal vaginal discharge, and laboratory findings (white blood cell count, platelet count, red blood cell count, hemoglobin count, hematocrit level, urinalysis and microbiology results). The statistical differences amongst categorical and numerical data were analyzed using the Chi-Square test and the Mann-Whitney test. Based on the patient’s history and the examination results, we suspected genital tract infections in22.52% (25/111)of subjects. All of them had abnormal vaginal discharge despite only one case had been confirmed as streptococcal infection. This study found that the majority of mothers with probable genital tract infection hadpreterm premature rupture of the membrane whilst preeclampsiawas more evident in those without genital tract infection. We conclude that genital tract infection during pregnancy is a significant contributor to the occurence of premature birth so that microbiological testing is needed to confirm the diagnosis.